An examination of inmate adjustment stratified by time served in prison. (September 2019) - Butler, H. Daniel
Abstract: Purpose: Differential Coercion and Social Support (DCSS) theory is used to examine whether sources of coercion and social support differ in their effects on inmate adjustment across periods of time served (< 1 year, 1–5 years, and > 5 years). Method and results: A nationally representative sample of male offenders incarcerated in state prisons is used to examine whether coercion (e.g., confinement in restrictive housing, victimization) and social support (e.g., perceptions of procedural justice and visits) influence assault misconducts, institutionalized resistance, and mental health outcomes across different periods of time served. The analytical strategy includes several binary logistic regressions with robust standard errors in addition to examining differences in predicted probabilities across models through average discrete changes (ADC). Sources of coercion, such as confinement in restrictive housing, largely influence each of the outcomes across periods of time served in prison, whereas sources of social support have mixed effects. However, there is limited variability in the magnitude of the effects across categories of time served. Conclusion: DCSS provides an understanding of how inmates may adjust differently to the prison environment based upon the amount of time that is served in prison. Interventions and treatment programs should focus on developing prosocial interpersonal relations between inmates and correctional staff. Highlights: Limited research has examined whether factors associated with inmate adjustment are time invariant. The National Inmate Survey, 2011–2012 is used to examine inmate adjustment across categories of time served in prison. Differential Coercion and Social Support Theory (DCSS) explains how in-prison experiences influence adjustment. Sources of coercion and social support do not differ in magnitude substantively across the categories of time served.